A multiple criteria decision making framework for regional aquaculture development - El-Gayar, Omar F.; Leung, PingSun (European journal of operational research, 2001)
Aquaculture development is considered as a viable source for providing high quality cheap protein, particularly, for developing countries where protein shortage already exists. However, complexities in such development planning can be difficult without the aid of modern decision-aids such as multiple criteria decision making (MCDM) models. MCDM models are already in use in the business and manufacturing sectors. However, their use in agriculture is limited and their use in aquaculture is almost nonexistent. This paper presents a MCDM framework for the planning of regional aquaculture development. The MCDM model seeks a desirable allocation of resources and activity levels that strikes an acceptable balance among the various development goals under consideration subject to resource constraints, market constraints, and pollution constraints. To accommodate different decision situations, three different MCDM solution techniques are implemented, namely, multiple objective programming (MOP), compromise programming (CP), and weighted goal programming (WGP). The applicability of the framework is demonstrated through applying it to a case study from northern Egypt where aquaculture is a viable industry for supplying cheap and good quality protein, balancing the foreign exchange deficits, and creating employment opportunities.